The Study of the Effect of Syntactic Complexity of Noun and Verb Phrase Structure on the Occurrence of Stuttering in 4-6 Year Pre-School Stuttering Persian Children - Abbas Ali Ahangar; Mehdi Bakhtiar; Mehdi Mohammadi; Maryam Shakeri-Kavaki (University of Social Welfare and Rehabilitation Sciences, 2013)
Objective: The purpose of the present research was to investigate the effect of syntactic complexity of noun phrase and verb phrase on the occurrence of stuttering in 4-6 year Persian speaking children with stuttering. Materials & Methods: This descriptive-analytic research was done on 15 stuttering children, consisting of 12 boys and 3 girls, 4 to 6 years old monolingual Persian speaking who referred to Javad-Ol-Aemmeh speech therapy clinic in Mashhad city. The sampling approach was simple (available) sampling method. To do this research, sampling was carried out in a quiet home of speech therapy where there were just the speech therapist, the parent, the child and the researcher. While speaking, the speech of the children was recorded by an MP3 with Creative brand. Finally, a 30-minute spontaneous speech sample was gathered from each of the given stuttering children. The children produced around 60 utterances during a verbal interaction with the speech therapist, parents (mother or father) or the researcher. Then the produced spontaneous speech sample by any of these stuttering children was transcribed on paper. The data were analyzed only as groups and not individually. The data were analyzed using SPSS software and Paired T-test method. Results: The group analyses showed significant differences between fluent and stuttered utterances in terms of syntactic complexity of noun and verb phrase structures. Also, the results confirm that at phrasal level, in noun phrases, based on their three functions as subject, direct object and object of preposition, there is a meaningful relationship between the number of subject (P<0.001) and object of preposition (P=0.050) with the stuttering frequency. In verb phrases, based on the presence of the auxiliary verb, copula verb, and negative prefix, just there is a meaningful relationship between the presence of the auxiliary verb and the stuttering frequency (P=0.010). Conclusion: The research findings indicate that, in Persian-speaking children, there is a meaningful relation between the variable of syntactic complexity, based on noun and verb phrase structure and the variable of stuttering frequency.